Pengaruh Suhu Pengeringan pada Viabilitas Agen Hayati Pelet BioferNA Berbahan Dasar Limbah Rumput Laut dan Pengaruhnya pada 2 Bibit Tanaman - sekar putri lisnanwati (AGRONISMA, 2022)
The seaweed industry's solid waste has the potential to be converted into organic fertilizer. The biological fertilizer used in this study was VP3 biological fertilizer, which is a liquid formulation fertilizer made from 3 functional bacterial isolates, molasses, and PEG 1% and vermiwash as a carrier. The goal of this study was to determine the ideal drying temperature for producing BioferNA pellet fertilizer made from waste seaweed. To determine their impact on plant growth, the drying results with the best total viability of biological agents will be tested on tomato and chili plant seeds. The design used in the Biological Agent Viability Test was Completely Randomized Design (CRD) with 10 treatments and was repeated 3 times. The design used in the test on plant seeds used a Completely Randomized Block Design (RCBD) which consisted of 5 treatments, and was repeated 4 times. All the observed data are analyzed statistically using analysis of variance (ANOVA) 5% significance level, if there is a significant difference betweem the treatments, it will have a further test using different test average with BNT at 5% significance level. The results showed that the drying temperature of BioferNA pellets made from seaweed waste had a significant effect on the total viability of biological agents. The drying temperature of 40°C has a higher average total viability of biological agents than the temperature of 50°C. BioferNA pellets made from seaweed waste, which were added with VP3 and Trichoderma viride FRP3, had a significant effect on seedling height and wet weight of chili and tomato seedlings, but had no significant effect on the root length of tomato seedlings. The observed growth parameters did not significantly affect the V1 (VP3) and V4 (VP3 + T. viride FRP3 + Vacuum) treatments.Keywords : VP3 Biofertilizer, Trichoderma viride FRP3, Seaweed Waste, Tomato, Chili